Data for "Quantitative Environmental Assessment of Explosive Residues from the Detonation of Insensitive High Explosive Filled 155 mm Artillery Shell" - Persico, Federica; Temple, Tracey; Ladyman, Melissa K.; Fawcett-Hirst, William; Gutierrez-Carazo, Encina; Coulon, Frederic (Cranfield University, 2022)
Following the detonation on a 155mm filled with an Insensitive High Explosive composition (IMX-104) composed by DNAN, NTO and RDX a sampling collection has been carried out to determine the residue deposition of the explosive residues. Half of a sampling arena (10m radius) has ben set up and filled with a 5 cm layer of sand. Samples have been collected in the area, following the Multi-Increment sampling technique, before and after the arena has been set up to determine if there was any cross-contamination after the detonation occurred. A rope has been used to create 2 x 2 m sections in which samples have been collected, following the multi-increment technique, in triplicates using spoons if sand was collected and sampling cores tools for soil. Samples have been stored at -20C for 3 months and t using the extraction technique by Temple et al, 2019 with Acetonitrile and water explosives residues have been analysed (always in triplicates).
Keywords: NTO; DNAN; RDX; Insensitive High Explosives; Environmental Science